Evaluasi Program Peremajaan Tanaman Kopi Arabika di Kabupaten Garut Menggunakan Policy Analysis Matrix (PAM) - Aminudin, Iwan; Ningsih, Nunung Isnaini Dwi; Kusnari, Tri (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
The coffee plant rejuvenation is one of the government programs for coffee commodities that has been carried out in several locations, one of which is in Garut Regency, West Java. To determine the success of this program, it is necessary to evaluate the Arabica coffee plant rejuvenation program in Garut Regency. The evaluation was conducted using the Policy analysis matrix (PAM). Respondents were Arabica coffee farmers selected through a purposive sampling method. 83 farmers out of 435 farmers who are members of 18 farmer groups were selected as respondents in this study. Primary data were obtained from questionnaires and secondary data were obtained from literature sources. The evaluation results showed that the Arabica coffee plant rejuvenation program had a competitive advantage as seen from two indicators, namely positive private benefits and Private Cost Ratio or PCR of 0.36 or < 1. The program also indicated that it had an impact on increasing profits for coffee farms in the research location as indicated by the value of PC > 1 (2.00). While the value of SRP>0 (0.22) indicates that the government program causes producers to spend less than the social cost of production. Overall, the Arabica coffee plant improvement program in Garut Regency has an impact on reducing the input costs of coffee farming increasing profits, and providing protection for coffee farmers.